Experimental investigation for RCC structural element using the sustainable material like Fly ash and Rice husk ash. (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Both the strain capacity at fracture and the tensile strength of unreinforced concrete are low. Traditionally, concrete has been strengthened by adding rice husk ash (RHA) to address these deficiencies. It is commonly recognized that Aggregate mixtures are heterogeneous in concrete, water, and cement. To create the desired properties in concrete, a variety of sustainable ingredients are added, including rice husk ash and fly ash. Proper component proportioning, mixing, and compacting are essential for producing strong, long-lasting concrete. A thorough experimental examination will be conducted to examine the impact of partially replacing cement in concrete with rice husk ash. Ash made from burning rice husks is an agricultural waste product with a high degree of reactivity. A by-product of the agriculture sector, rice husk ash (RHA) has a high silicon dioxide (SiO2) content. An effort was made to figure out the ideal burning temperature and duration. The ideal combination, according to the results, is 650 degrees Celsius and a burning time of 60 minutes. Afterwards, a number of tests were run to ascertain the characteristics of concretes with the ideal RHA.